The composition and predictive function of the fecal microbiota in female donkeys across different reproductive cycles - Xing, Jingya; Jia, Mingquan; Zhang, Guoliang; Li, Lanjie; Liu, Shuai; Li, Guangyu; Liu, Guiqin (Frontiers in Microbiology, 2025)
The microorganisms residing in the gastrointestinal tract of monogastric herbivores play a vital role in nutrient absorption and maintaining the host’s health. However, the quantitative and functional establishment of these microorganisms in female donkeys across different reproductive cycles has not yet been examined. Knowledge regarding the composition and function of gut microbiota in female donkeys during different reproductive cycles remains limited. By applying high-throughput sequencing technology and functional prediction applied to fecal samples from female donkeys across different reproductive cycles, we characterized their gut microbial composition and predicted their functional profiles. The fecal microbiota diversity in female donkeys showed no significant differences across different reproductive cycles through alpha diversity. However, the relative abundance of Firmicutes was higher during lactation, whereas Bacteroidetes were significantly higher during pregnancy. Principal coordinate analysis (PCoA) revealed the gut microbiota composition of pregnant female donkeys differed significantly from that in lactating and non-pregnant female donkeys. Bacteroidetes and Alloprevotella dominated during pregnancy in donkeys, while Firmicutes and unidentified Clostridiales were more prevalent during lactation. For functional prediction, there were significant differences in the relative abundance of pathways in the feces of female donkeys across different reproductive cycles, such as immune system processes, metabolism, glycan biosynthesis and metabolism, environmental adaptation and cell motility (p < 0.05 or p < 0.01). By correlating metabolic functions with microbial phyla, we suggest that metabolic and immune functions associated with the gut microbiota in lactating donkeys may be reduced compared to pregnant donkeys. Principal component analysis (PCA) revealed that the functional KEGG Orthologs (KOs) in the fecal microbiota of pregnant donkeys were distinctly separated from the lactation and non-pregnant female donkeys. Microbial community composition and structure exhibit distinct characteristics across different reproductive cycle, which are closely related to the functions of the microbiome. Our findings provide a foundation for understanding the compositional and functional differences in the microbial communities of mares’ feces across different reproductive cycles, offering valuable insights for the precise feeding of mares throughout different reproductive cycles.